2009
DOI: 10.1242/jeb.028456
|View full text |Cite
|
Sign up to set email alerts
|

Song competition changes the brain and behavior of a male songbird

Abstract: SUMMARY Males should adjust their behavior and its neural substrates according to the quality of competition that they assess by eavesdropping on other males'courtship signals. In European starlings (Sturnus vulgaris), females base mate choice, in part, on aspects of male song associated with its length,which positively correlates with the males' reproductive success,immunocompetence, age and ability to repel competing males. To determine how variation in the quality of male courtship song affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…Using previously described protocols [33], we fixed one hemisphere (alternating left and right between subjects within each treatment group) in 5% acrolein, saturated it with 30% sucrose for cryoprotection, froze it on dry ice and held it at −80°C for approximately two weeks until Nissl staining was conducted. The second hemisphere was fresh frozen on dry ice and held at −80°C until brain regions were micropunched and HPLC was conducted (ca.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using previously described protocols [33], we fixed one hemisphere (alternating left and right between subjects within each treatment group) in 5% acrolein, saturated it with 30% sucrose for cryoprotection, froze it on dry ice and held it at −80°C for approximately two weeks until Nissl staining was conducted. The second hemisphere was fresh frozen on dry ice and held at −80°C until brain regions were micropunched and HPLC was conducted (ca.…”
Section: Methodsmentioning
confidence: 99%
“…Using micropunches (Fine Science Tools, Foster City, CA, USA), we took one tissue sample from each of four brain regions – the NCM and the CMM of the auditory telencephalon; the principal nucleus of the anterior forebrain pathway of the song control system, area X, and the principal nucleus of the motor pathway, RA. We chose brain sections containing each region based on boundaries defined by Nissl-staining ([33] for protocol) in sections from the alternate, fixed hemisphere and comparison with a zebra finch atlas [71]. Although inter-hemispheric differences in anatomy and plane of section could lead to errors when using one hemisphere (the Nissl stained one) to guide dissection in the other, we used punches with diameters well below the diameters of the brain regions of interest to ensure that we included only tissue that was within the targeted brain region.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Small, Brenowitz, & Moore, 2007). Social context also influences male singing and song system anatomy (Sartor & Ball, 2005;Sockman, Salvante, Racke, Campbell, & Whitman, 2009;Strand, Ross, Weiss, & Deviche, 2008), and the volumes of male song nuclei vary with social status in species with complex social organization of breeding units. For example, dominant males of the white-browed sparrow weaver, Plocepasser mahali, have larger HVC and RA volumes and differ from subordinate males in the cellular machinery and gene expression patterns in these nuclei (Voigt & Gahr, 2011;Voigt, Leitner, & Gahr, 2007).…”
mentioning
confidence: 99%
“…We found a weak positive relationship between the number of male nest-mates and HVC volume, the inverse of the expected relationship if male nest-mates inhibit singing behavior. Sockman et al (2009) showed that European starlings exposed to playback of long songs developed larger RA than those exposed to short song, suggesting a stimulatory effect of listening to the song of others, which might explain the weak positive relationship between HVC and number of male nest-mates found here.…”
Section: Discussionmentioning
confidence: 58%